Imagining an Asian American Superhero of North Korean Origin: A Design Fiction - Seo-Young Chu (Sungkyunkwan, 2021)
My talk, a thought-experimental blend of literary criticism and speculative “design fiction,” will introduce you to an Asian American superhero of North Korean origin. In this science-fictional superhero, whom I have tentatively named “구름”/”☁️”/“Ku-reum,” Korea’s elusive realities coalesce into legible form. More specifically, they become available for narrative experience and relatable to us as an anthropomorphic character, a person with whom we might identify, come face-to-face, sympathize, interact dynamically, and have a conversation. Ku-reum is designed to reflect Korea’s complex past and hopes for the future. Existing beyond division systems, Ku-reum uses the non-binary pronouns “one”/“they.” Neither “South” nor “North,” neither “East” nor “West,” Ku-reum transcends the four cardinal directions. (Magnetic compasses break down in one’s/their presence.) While genetically related to the South Korean Marvel superheroes Taegukgi and Ami Han/White Fox (among others), Ku-reum is unique. One’s/their superpowers—in which Korean shamanism and geomancy are enhanced by cutting-edge technologies and complicated by vulnerabilities such as Americanized han—include time travel, self-cloning, telepathy, the ability to choreograph the flow of 기, the ability to channel hwabyung into creative energy and cathartic release, and the ability to bend the 38th parallel. Superpowered characters like Ku-reum can be designed and ”tried on” as if they were prosthetic suits or exoskeletons that extend the human sensorium and mobilize our sense of agency. To “try on” such exoskeletons is to experiment with new ways of navigating through and actively participating in Korea’s cognitively estranging pasts, presents, and futures.